1981
DOI: 10.1161/01.str.12.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Focal cerebral ischemia measured by the intra-arterial 133xenon method. Limitations of 2-dimensional blood flow measurements.

Abstract: SUMMARY The limitations of 2-dlmendooal isotope techniques in the study of focal cerebral ischemia were investigated using the intra-carotid '"xenon injection method and a 254 multidetector scintillation camera. To make sure that the detectors "look" directly on infarcted areas, only patients with infarcts involving cortical surface structures were included in the study. Eleven such patients were found among 43 consecutive patients with completed stroke, all investigated with CT-scan. The blood supply to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Abundant evidence of such a development is accumulated in the literature 8 32 -42~52 and the following other possible explanations can be ruled out: 1) The severely hyperemic areas cannot be collaterally perfused areas: The early filling veins draining the hyperemic areas were not localised distal to the occlusion as would be expected if these areas were collaterally perfused-they were localised proximal to the occlusion. The angiograms as well as the isotopeangiograms 29 obtained in connection with the flow study clearly showed that the areas were filled anterogradely and as expected very rapidly. Collaterally perfused areas in patients with MCA occlusion moreover appears to be low flow areas rather than hyperemic areas in the acute state.…”
Section: Severe Hyperemia a Sign Of Spontaneous Arterial Reopening Asupporting
confidence: 71%
“…Abundant evidence of such a development is accumulated in the literature 8 32 -42~52 and the following other possible explanations can be ruled out: 1) The severely hyperemic areas cannot be collaterally perfused areas: The early filling veins draining the hyperemic areas were not localised distal to the occlusion as would be expected if these areas were collaterally perfused-they were localised proximal to the occlusion. The angiograms as well as the isotopeangiograms 29 obtained in connection with the flow study clearly showed that the areas were filled anterogradely and as expected very rapidly. Collaterally perfused areas in patients with MCA occlusion moreover appears to be low flow areas rather than hyperemic areas in the acute state.…”
Section: Severe Hyperemia a Sign Of Spontaneous Arterial Reopening Asupporting
confidence: 71%
“…As reported from our laboratory at least 40% of the counts originate from isotope deposited (and washed out) in surrounding areas with a higher flow. 15 This accords quite well with the estimates of Bolmsjo 19 showing that, for a 3.3 cm 2 area "seen" with a narrow collimator ("fine hole") as used in the present study, 28% to 41% of ipsilateral cortical counts were scattered from extraregional sources. Thus, the washout curve obtained from a low flow area is the sum of the washout of isotope actually deposited in the low flow area (this represents true flow) and the washout of Compton-scattered radiation from the surroundings (with a higher flow).…”
Section: Methodological Considerations and Interpretation Of Datasupporting
confidence: 92%
“…A major disadvantage of this method is that CBF in low flow areas is heavily overestimated because of scattered radiation (Compton scatter). 12,15 Moreover, true changes of CBF in the low flow area are in many cases difficult or impossible to detect because of Compton scatter.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 With the Xenon-133 intraarterial injection method CBF must decrease by 15% or more in order to be considered significantly reduced. 19 Because of Compton scatter, focal CBF reductions, however, become underestimated with the Xenon-133 techniques. When measuring a focal CBF reduction of 15% it should be remembered that the true CBF reduction in the area is about 20%.…”
Section: Migraine Without Aura: Does Vasospasm Occur? Is Cbf Reduced?mentioning
confidence: 99%